ANALISIS PENGARUH DIMENSI KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI TOKO CERME PURBALINGGA - Asrillia, Auriel Yeristha; Amalia, Shella Rizqi; Masrokhah, Siti (Awatara Publisher, 2023)
Analysis of the influence of service quality on purchasing decisions at the Cerme Purbalingga Store. This study aims to determine the effect of tangible, responsiveness, reliability, assurance, empathy on consumer purchasing decisions at Toko Cerme Purbalingga. Determination of the sample used in this study 100 respondents with purposive sampling technique. The data obtained were processed using SPSS 25. The analytical method used in this study was multiple linear regression. The results of the study show that service quality simultaneously has a significant effect on purchasing decisions. Partially, reliability, responsiveness, and assurance have no significant effect on purchasing decisions. Tangible and empathy variables are variables that have a significant influence on purchasing decisions.